2020
DOI: 10.1038/s41598-020-58900-z
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and clinical correlates of neoplastic transformation in gastric hyperplastic polyps in Chinese patients

Abstract: remain unknown. This study aimed to analyze possible risk factors that are associated with the neoplastic transformation of gastric hyperplastic polyps. Results Demographics features. During January 2010 and June 2017, there were 6418 cases of gastric polyp diagnosed. 1115 of these (17.4%, 1115/6418) were histologically confirmed GHPs. 30 of these GHPs (2.69%, 30/1115) were diagnosed as containing dysplasia or adenocarcinoma. The mean age was 61.73 ± 9.024 years old (range 32-79). Absence of Helicobacter pylor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…In the recent studies, H. pylori's positivity rates in the HPs are similar with the present study. Yu et al and Hu et al found that H. pylori's positivity rates are 22.7% and 36.4%, respectively (17,18). Also, the study of Nam et al showed that H. pylori's eradication caused regression in HPs (19).…”
Section: Discussionmentioning
confidence: 97%
“…In the recent studies, H. pylori's positivity rates in the HPs are similar with the present study. Yu et al and Hu et al found that H. pylori's positivity rates are 22.7% and 36.4%, respectively (17,18). Also, the study of Nam et al showed that H. pylori's eradication caused regression in HPs (19).…”
Section: Discussionmentioning
confidence: 97%
“…In our case, H. pylori infection was negative, and no atrophy of the gastric mucosa evaluated by endoscopy was found. Moreover, previous studies of the pathogenesis of gastric hyperplastic polyps have shown that hypergastrinemia induced by severe atrophic gastritis of the corpus ( 25 - 29 ) or prolonged use of PPIs might induce the development of gastric hyperplastic polys ( 28 , 32 , 33 ). Gastrin has trophic effects on the gastrointestinal mucosa ( 34 ) and may repair gastric mucosal damage caused by APC.…”
Section: Discussionmentioning
confidence: 99%
“…However, rare cases of gastric polyps developing after APC therapy for GAVE have been reported ( 14 - 20 ) and termed “portal hypertension-associated polyps” or “portal hypertensive polyps” ( 21 - 24 ). The pathogenesis of gastric hyperplastic polyps is still unknown, but it is thought that the exaggerated repair of mucosal damage ( 25 , 26 ) or hypergastrinemia may play a role in the development of the polyps ( 27 - 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, fundic argyrophil hyperplasia which reflects hyperplasia of ECL cells and thus hypergastrinemia, was already in 1984 described to be associated to HPs [ 92 ]. A trend towards hypergastrinemia as risk factor for malignant progression of hyperplastic polyps has also been reported [ 93 ]. The prevalence of dysplasia in sporadic hyperplastic polyps has been reported to be in the range 1.9–19% [ 94 ], with a marked association with size [ 95 ].…”
Section: Gastric Polypsmentioning
confidence: 99%